2019
DOI: 10.2478/cjf-2019-0016
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Extant Croatian Freshwater Fish and Lampreys

Abstract: A checklist of the freshwater fish fauna of Croatia is presented for the first time. It is based on 1360 publications of historical and recent data in the literature. According to the literature review, there were 137 fish species in 30 families and 75 genera recorded in Croatia. The checklist is systematically arranged and provides distributional data of the freshwater fish fauna as well as whether the species is endemic, introduced or translocated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 214 publications
2
38
0
Order By: Relevance
“…4) but a formal description did not follow. In the most recent review of Croatian freshwater fishes (Ćaleta et al 2019) the presence of S. microlepis in the Cetina is considered as not confirmed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4) but a formal description did not follow. In the most recent review of Croatian freshwater fishes (Ćaleta et al 2019) the presence of S. microlepis in the Cetina is considered as not confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Recent summarising publications (Habeković and Pažur 1995; Bănărescu and Herzig-Straschil 1998; Bogut et al 2006; Mrakovčić et al 2006, 2016; Kottelat and Freyhof 2007; Zupančič 2008; Šanda et al 2009; Ćaleta et al 2015, 2019) indicate that the range of S. microlepis encompasses the entire karst system of the Culuša – Ričina – Brina – Suvaja – Matica – Vrljika – Tihaljina – Mlade – Trebižat (a single river interrupted by underground sections, a tributary to the Neretva) downstream to the waterfall Kravice. In this karst river system, it occurs in basins of the Prološko Blato Lake and the Ričice Reservoir in the Imotski region in Croatia and in Krenica Lake and the Matica, Vrljika, Tihaljina and Trebižat rivers in Bosnia and Herzegovina.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…K. panizzae was reported in 34 Natura 2000 sites, 25 of whose are coastal lagoons (Table 3) distributed along the Adriatic coast both on Italian and Balkan side [81,82]. However, recent phylogenetic studies, based on mitochondrial DNA analysis, have shown that K. mrakovcici, K. radovici and K. panizzae are not distinct species and are all K. panizzae [12], so the distribution range of the species should be reconsidered.…”
Section: Conservation Statusmentioning
confidence: 99%
“…Well-structured populations are present in the lagoon of Venice [80,88] and in the basins of the Comacchio lagoons [67]. However, since this species does not tolerate salinity over 30, it is often also observed in oligohaline and freshwater environments [87], in some of which it was introduced accidentally, i.e., Trasimeno Lake in Italy [92] and reservoir of the Ričica River in Croatia [82,93]. Records were also made in Bosnia-Herzegovina, in the freshwaters of the coastal lake Svitava in the Neretve basin [94].…”
Section: Biology and Distributionmentioning
confidence: 99%